Anti-factor Xa activities of zingerone with anti-platelet aggregation activity. (July 2017) - Lee, Wonhwa; Ku, Sae-Kwang; Kim, Mi-Ae; Bae, Jong-Sup
Abstract: Zingerone (ZGR), a phenolic alkanone found in Zingiber officinale, has been reported to have various pharmacological activities such as anti-inflammatory, anti-apoptotic, and protecting myocardial infarction and irritable bowel disorder. The aim was to identify the unreported bioactive anti-factor Xa (FXa) and anti-platelet activities of ZGR. ZGR was evaluated for their anti-FXa and anti-platelet aggregation properties by monitoring clotting time, platelet aggregation, FXa activity and production, and thrombus formation. ZGR reduced activated partial thromboplastin time and it inhibited the catalytic activity of FXa toward its substrate S-2222 in a noncompetitive inhibition model and inhibited platelet aggregation induced by adenosine diphosphate (ADP) and U46619 (not thrombin). However, ZGR did not prolong bleeding time in mice, as shown by tail clipping. ZGR also inhibited ADP- and U46619- induced phosphorylation of myristolated alanine-rich C-kinase substrate (MARCKS) and the expressions of P-selectin and PAC-1 in platelets. In an animal model of arterial and pulmonary thrombosis, ZGR showed enhanced antithrombotic effects. ZGR also elicited anticoagulant effects in mice. Our results reveal that ZGR is an antithrombotic compound with both FXa inhibitory and anti-platelet aggregation activities. Collectively, these results show that ZGR could serve as candidates and provide scaffolds for the development of new anti-FXa and anti-platelet drugs. Graphical abstract: Highlights: Zingerone, found in Zingiber officinale, prolonged coagulation time. Zingerone inhibited the activities and productions of FXa. Zingerone inhibited the platelet aggregation. ZGR showed enhanced antithrombotic effects in vivo.